Peningkatan Pemahaman Konsep Matematika Siswa Kelas VII Melalui Strategi Pembelajaran Mendalam (Deep Learning) - Sabar Dumayanti Sihombing; Mesriana Pandiangan; Valentina Margaretha Marbun; Tasya Kumala Ningrum; Ersa Manora Pardede; Christin Ruth D. Sipahutar; Kristina Sianipar; Novita Sari Emelia Manalu (MAN 4 Kota Pekanbaru, 2026)
Conceptual understanding plays a crucial role in mathematics learning; however, classroom practices that prioritize procedural execution often hinder students’ ability to construct meaning from mathematical ideas. This issue was observed among seventh-grade students at SMP Cinta Rakyat 3 Pematangsiantar, where problem-solving activities were largely approached through formula memorization rather than conceptual reasoning. This study investigates the extent to which a pedagogical deep learning strategy, defined as a high-level cognitive approach distinct from artificial intelligence, can enhance students’ mathematical conceptual understanding by fostering active engagement, conceptual exploration, and reflective thinking. The research adopted a quantitative approach with a pre-experimental one-group pretest–posttest design involving 32 students selected through purposive sampling. Students’ understanding was assessed using an essay-based instrument aligned with indicators of conceptual comprehension. Data were examined through descriptive analysis, normality testing, paired-sample t-test, and the calculation of the Normalized Gain (N-Gain) index. The findings reveal a meaningful increase in conceptual understanding following the intervention, indicated by a significant difference between pretest and posttest scores and an average N-Gain of 0.62, classified as a moderate level of improvement. These results highlight the potential of deep learning-oriented instructional practices to support deeper conceptual engagement in mathematics learning. While the absence of a control group restricts broader generalization, the study offers preliminary empirical insight into the effectiveness of deep learning strategies within junior high school mathematics contexts.